Matching of an observed event and its virtual model in relation to smart theories, coupled models and supervision of complex procedures—A review - Razek, Adel (Comptes Rendus. Physique)
This contribution aims to illustrate the nature of the observation–modeling (or real–virtual) link, the importance of the exact model (or coupled model) in the matching involved in this link and the use of this link in the supervision of complex procedures. This involves offline and real-time matching practices. The offline case is mainly about the management and ruling of elegant theories and computational tools mimicking physical paradigms. Real-time pairing notably concerns natural phenomena, autonomous automated systems and complex procedures. The paper assesses, analyzes and discusses the different elements mentioned. This is aided by a literature review.